Effect of Different Gel Etchants and Two Etching Times on Shear Bond Strength to Bovine Dentin of an Etch and Rinse 2-Step Adhesive System/Jose Gabriel M. Cadiz, Katherine S. Ejipto and Madeleine M. Rayos. - Cadiz, Jose Gabriel M.; Ejipto, Katherine S.
INTRODUCTION: The COVID-19 pandemic has impacted the lives of individuals, changing their daily routine due to implemented measures to prevent spread of the virus. These measures have led to various challenges including limited access to dental care, thus emphasizing the need for at-home preventive measures. This study aimed to compare the oral hygiene practices (OHP) and oral health seeking behavior (OHSB) of students (A.Y 2022-2023) of University of the Philippines Manila (UPM) pre pandemic and during the COVID-19 pandemic.